2014
DOI: 10.3109/13880209.2013.836721
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of raw and cooked blackcurrant extract on DNA damage induced by hydrogen peroxide in human lymphoblastoid cells

Abstract: Context: Blackcurrant (Ribes nigrum L.) is a classical fruit that has long been used to make juice, liqueur and sometimes medicines in Europe. The beneficial effects of blackcurrant, which are inhibition of lipopolysaccharide-stimulated inflammatory, anticarcinogenesis and other health effects, have been reported. Objective: Previously, we reported the antimutagenic activities of blackcurrant using a yeast gene mutation assay. In this study, we investigated whether this antimutagenicity of blackcurrant was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…The extract of one Australian fruit (among several studied) caused an increase in MN [48]. Other reports are of protection against oxidation damage caused by H 2 O 2 [43,44,46]; or tert-butyl-hydroperoxide (t-BOOH) [45,49]. The exception to usage of high doses is a report by Bellion et al [47] with apple polyphenol extracts; they found that 24 h pre-incubation of Caco2 cells decreased the DNA damage induced by menadione (low concentrations actually giving the greatest protection).…”
Section: Resultsmentioning
confidence: 99%
“…The extract of one Australian fruit (among several studied) caused an increase in MN [48]. Other reports are of protection against oxidation damage caused by H 2 O 2 [43,44,46]; or tert-butyl-hydroperoxide (t-BOOH) [45,49]. The exception to usage of high doses is a report by Bellion et al [47] with apple polyphenol extracts; they found that 24 h pre-incubation of Caco2 cells decreased the DNA damage induced by menadione (low concentrations actually giving the greatest protection).…”
Section: Resultsmentioning
confidence: 99%
“…TK6 was exposed to γ-irradiation at doses of 0.125, 0.250, 0.500, and 1.000 Gy with or without 1.0 mg/mL BCE, a concentration that was decided in accordance with a previous study [ 3 ]. The dose rate was 1.0 Gy/min (Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, we reported that extracts of mature and premature blackcurrant produced in Aomori Prefecture had high anti-oxidant and anti-genotoxic activities, as evaluated using a yeast loss-of-heterozygosity (LOH) assay, an in vitro comet assay to evaluate DNA damage, and a micronucleus (MN) test to screen for genotoxic compounds in human TK6 lymphoblastoid cells [ 2 , 3 ]. In the yeast LOH assay, blackcurrant extracts (BCEs) extracted from premature and mature fruits suppressed gene mutations induced by hydrogen peroxide (H 2 O 2 ), methyl methanesulfonate (MMS), and ultraviolet (UV) radiation [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Delphinidin-3-rutinoside and cyanidin-3-rutinoside are specific blackcurrant anthocyanins (2). These blackcurrant constituents have been associated with certain health benefits, including improved blood flow (5), decreased inflammatory marker levels (6) and protection against DNA damage induced by hydrogen peroxide (7).…”
Section: Introductionmentioning
confidence: 99%